Quality culture, university-industry collaboration, and perceived employability among vocational students in China: a Yanpei Huang perspective - Li, Hui; Khattak, Shoukat Iqbal; Shamim, Muhammed Asif (Frontiers in Psychology, 2024)
Students' perceived employability (SPE) can be seen as one of the indicators of technical and vocational education and training (TVET) quality. However, less is known about the determining factors of SPE in vocational education. As the founder of modern vocational education in China, Yanpei Huang has written a large volume on ensuring students' employability and the quality culture of TVET. Nowadays, as the feature and nature of TVET, university-industry collaboration (UIC) has been promoted worldwide. The primary objective of this study was to investigate the influence of quality culture from Yanpei Huang's perspective (YHQC) on the SPE and the UIC role in the relationship between YHQC and SPE in a TVET university in China. Data were collected by questionnaire from 341 students from one vocational education university in China. The questionnaire included measures of quality culture, perceived employability, and UIC. The Structural Equation Modelling by AMOS 25 was used to test the proposed hypothesis. The results indicate that YHQC acts as a significant factor in enhancing SPE, and UIC is found to act as a partial mediator in this relationship. This study has contributed to the literature and practices by presenting a comprehensive quality culture from Yanpei Huang's perspective, confirming the above relationship, and providing practical suggestions for stakeholders to develop a quality culture in TVET institutes, promote UIC, and enhance SPE.